Coleus Amboinicus exhibits anti-microbial and anti-fungus activities and having no toxicity at highest doses assessed in mice - Khattak, Muhammad Muzaffar Ali Khan; Bakhtiar, M. Taher; Abdul Rahman, Suzanah; Damanik , Rizal; Yahaya, Azhary (2012)
Plants leaves of Coleus amboinicus from Indonesia (CAL-I) and from Malaysia, Coleus aromaticus (CAT-M), Pogostemon cablin (PC-M), Coleus blumei–red leaves (CBR-M), Coleus amboinicus– (CAL-M) Coleus blumei –purple leaves (CBP-M) were collected, freeze dried and extracted with aqueous methanol. The biological activity in vitro, in relation to total phenolic, flavonoid & antioxidants contents and antimicrobial & antifungal activities were assessed. Total phenolics & antioxidants activities, antimicrobial & anti-fungal activities and toxicity were determined by using appropriate methods. The phenolic content among the extracts of leaves showed significant (p<0.05) difference ranging from 55.21 - 95.17 mg GAE/g of dried samples. The PC-M had the highest contents of phenolics followed by CBP-M. There were significant (p<0.05) differences in IC50 values ranging from 10.5 – 34.1 µg/ml. Among the species studied, CAL-M and PC-M showed higher antioxidants activities compared to the rest of the extracts. The extracts showed activities against bacteria and fungus and resulted in significant (p<0.05) differences between activities against microorganisms and fungus. The minimum inhibitory concentration of all leaves extracts ranged from 1.0–2.0 mg/ml in inhibiting the growth of S. aureus, E. coli, P. aeruginosa and B.subtilis. The acute toxicity test revealed that there was no mortality even at the highest doses levels used in mice i.e. 5000 mg/kg body weight. This study shows that the extracts can be used as antioxidants and antimicrobial agent without having any toxic effect. Furthermore, the anti- antimicrobial & anti-fungal activities relates to the concentration of total phenolic, flavonoid and antioxidants in the extracts.